# user friendly proof of fundamental theorem of calculus

Silly question. Can someone show me a nice easy to follow proof on the fundamental theorem of calculus. More specifically,

$\displaystyle\int_{a}^{b}f(x)dx = F(b) - F(a)$

I know that by just googling fundamental theorem of calculus, one can get all sorts of answers, but for some odd reason I have a hard time following the arguments.

• Are you familiar with the Riemann sum definition of the integral?
– user99914
Commented May 2, 2015 at 2:24
• There is no real easy proof of this, it's a deep fact. The best intuition is to think of the anti-derivative as keeping a running sum of the accumulation of the area, where the sum is taken to the limit. Commented May 2, 2015 at 2:29
• What conditions do you want on $f$? Commented May 2, 2015 at 2:36

To understand this you will also need to understand the first FTC, and I will show you this. (As you said there may be more than one proof, I will base mine on one similar given in the Stewart calculus books).

You may notice during the proof of the first already the connectedness to the derivative which I assume you are familiar with.

$$\mathbf{FTC 1:}$$ If $$f$$ is continuous on $$[a,b]$$ then the function g defined by

$$g(x)= \int_{a}^{x} f(t)dt$$ for $$a \le x \le b$$ is continuos on $$[a,b]$$ and differentiable on $$(a,b)$$ , and $$g'(x)=f(x)$$.

$$\mathbf{Proof:}$$

Suppose we have $$x$$ and $$x+h$$ in $$(a,b)$$, then we have

$$g(x+h)-g(x)= \int_{a}^{x+h}f(t)dt-\int_{a}^{x}f(t)dt$$ $$=\int_{a}^{x}f(t)dt+\int_{x}^{x+h}f(t)dt-\int_{a}^{x}f(t)dt$$

$$=\int_{x}^{x+h}f(t)dt$$

Thus, we have for $$h \neq 0$$

$$\frac{g(x+h)-g(x)}{h}=\frac{1}{h}\int_{x}^{x+h}f(t)dt$$

If we assume $$h \gt 0$$ , since f is continuous on $$[x,x+h]$$ the "Extreme Value Theorem" says that there exist some numbers, u and v in the closed interval $$[x,x+h]$$ such that $$f(u)=m$$ and $$f(v)=M$$ where $$m$$ and $$M$$ represent the inf and sup of the interval respectively.

Thus, by further properties of Riemann integral

$$mh \le \int_{x}^{x+h}f(t)dt \le Mh$$

$$\rightarrow$$

$$f(u)h \le \int_{x}^{x+h}f(t)dt \le f(v)h$$

$$\rightarrow$$

$$f(u) \le \frac{1}{h} \int_{x}^{x+h}f(t)dt \le f(v)$$

ie,

$$f(u) \le \frac{g(x+h)-g(x)}{h} \le f(v)$$

( If $$h \lt 0$$ the same argument can be repeated with small changes)

so now we invoke limits,

Let $$h \to 0$$ , then you can see that $$u \to x$$ and $$v \to x$$ , ( it is clear from the interval they are in).

So both sides' limits are the same, thus the limit exists and we have,

$$g'(x)=\lim_{h \to 0} \frac{g(x+h)-g(x)}{h}=f(x)$$

thus , we finally have $$\frac{d}{dx}\int_{a}^{x}f(t)dt=f(x)$$

$$\mathbf{FTC2:}$$ If f is continuous on $$[a,b]$$, then $$\int_{a}^{b}f(x)dx=F(b)-F(a)$$, where F is any antiderivative of f, that is $$F'=f$$.

$$\mathbf{Proof:}$$

Let $$g(x)= \int_{a}^{x}f(t)dt$$, then from FTC1 we have that $$g'(x)=f(x)$$

That is, g is an antiderivative of f. Now, if there is another antiderivative of f, say F, on the same closed interval [a,b] then we know the only difference they can have is a constant,

$$F(x)=g(x)+C$$.

Consider $$g(a)=\int_{a}^{a}f(t)dt=0$$

Now consider,

$$F(b)-F(a)=[g(b)+C]-[g(a)+C]$$

$$=g(b)-g(a)=g(b)$$ $$= \int_{a}^{b} f(t)dt$$

i will assume that $f$ is continuous, $F$ is differentiable in $(a,b)$ and $$F'(x)=f(x).$$ we will need the mean value theorem in the form $$\text{ for any } a \le c, d < \le b,\quad F(d) - F(c) = (d-c)F'(t) = (d-c)f(t) \text{ for some } c < t < d.$$

let $a \le x_0 \le x_1\le \cdots\le x_n = b$ any partition of $[a, b].$ then \begin{align}F(b) - F(a) &= \left(F(x_n) - F(x_{n-1}\right) + \cdots +\left(F(x_j) - F(x_{j-1}\right)+\cdots+\left(F(x_1) - F(x_{0}\right)\\ &=(x_n-x_{n-1})f(t_n)+\cdots+(x_j-x_{j-1})f(t_j)+\cdots+(x_1-x_0)f(t_1)\\ &=\int_a^bf(x)\, dx.\end{align}

• I think you will need a bit more justification in the last line. What you have shown is that if $P$ is any partition of $[a, b]$ then $F(b) - F(a)$ can be regarded as a Riemann Sum of $f$ over $[a, b]$. But a Riemann Sum is not necessary equal to Riemann integral. In this case since $F(b) - F(a)$ is a Riemann for every partition $P$, it follows that it lies between every lower darboux sum and every upper darboux sum and since $f$ is integrable, $F(b) - F(a)$ is the unique limit of lower and upper darboux sum and therefore is the Riemann integral of $f$ over $[a, b]$. Commented May 3, 2015 at 9:34

The key fact is that, if $$f$$ is continuous, the function $$G(x)=\int_a^xf(t)\,dt$$ is an antiderivative for $$f$$. For this, $$\frac1h\,\left(\int_a^{x+h}f(t)\,dt-\int_a^xf(t)\,dt\right) =\frac1h\,\int_x^{x+h}f(t)\,dt\xrightarrow[h\to0]{}f(x).$$ The justification of the limit basically plays on the fact that $$f$$ is continuous. A formal proof requires dealing with the formal definition of continuity. Namely, given $$\varepsilon>0$$ by definition of continuity there exists $$\delta>0$$ such that $$|f(x)-f(t)|<\varepsilon$$ whenever $$|x-y|<\delta$$. If we choose $$h<\delta$$, then $$|f(t)-f(x)|<\varepsilon$$ for all $$t\in [x,x+h]$$. Then \begin{align} f(x)&=\frac1h\int_x^{x+h}f(x)\,dt\leq\frac1h\int_x^{x+h}(\varepsilon +f(t))\,dt=\varepsilon + \frac1h\int_x^{x+h}f(t)\,dt\\[0.3cm] &\leq2\varepsilon + \frac1h\int_x^{x+h}f(t)\,dt=2\varepsilon+f(x). \end{align} Thus $$f(x)-\varepsilon\leq \frac1h\int_x^{x+h}f(t)\,dt\leq f(x)+\varepsilon,$$ showing the convergence.

Now $$G(a)=0$$, and $$G(b)-G(a)=G(b)=\int_a^bf(t)\,dt$$. If $$F$$ is any other antiderivative of $$f$$, we have $$F'=f=G'$$, so $$(G-F)'=G'-F'=0$$, i .e. $$G(x)-F(x)=c$$ for some constant. That is, $$F(x)=G(x)-c$$. Then $$F(b)-F(a)=(G(b)-c)-(G(a)-c)=G(b)-G(a)=\int_a^bf(t)\,dt.$$